Effect of nasal irrigation in adults infected with Omicron variant of COVID-19: A quasi-experimental study - Li Liu; Shuangshuang Xie; Cheng Li; Liang Su; Chengbao Zhu (Frontiers Media S.A., 2023)
ObjectiveTo investigate the effect of nasal irrigation on the duration of symptoms and nucleic acid conversion in adults infected with the Omicron variant of COVID-19.MethodsThis quasi-experimental study enrolled patients diagnosed with asymptomatic, mild, or moderate Omicron infection at the Shandong Public Health Clinical Center between April 1, 2022 and May 1, 2022. Patients were divided into two groups to receive Lianhua Qingwen granules and traditional Chinese medicine (TCM) prescriptions (conventional group) and 3% hypertonic saline nasal irrigation based on conventional treatment (nasal irrigation groups), respectively. Primary outcomes were symptom disappearance time and nucleic acid negative conversion time. Secondary outcomes were peripheral blood white blood cell (WBC), lymphocyte (LYM) count, neutrophil (NEU) count, C-reactive protein (CRP) level, and chest CT examination findings.ResultsEighty patients were included (40 patients/group). Multiple linear regression analysis showed that, after adjustment for comorbidities, smoking history, LYM count, and Ct values of N gene, the patients in the nasal irrigation group were more likely to get lower nucleic acid negative conversion time (β = −11.052, 95% CI: −8.277-13.827, P < 0.001) compared with the conventional group. The symptom disappearance time showed no significant improvement (P > 0.05). Subgroup analysis for treatment-naïve patients in the nasal irrigation group showed similar nucleic acid negative conversion time improvement (P = 0.038).ConclusionEarly nasal irrigation shortens the nucleic acid negative conversion time in adults infected with the Omicron variant but without improvements in symptom disappearance time.